PETROGRAPHY OF PYROCLASTIC ROCK MOUNT MASURAI JAMBI PROVINCE - Kirana, Febiyora Chandra; Nuriil Tadersi, Risnaliyah; Hasbullah, Andrea; Siregar, Anggi Deliana; Ritonga, D.M Magdalena; Utama, Hari Wiki; Misnawati, Misnawati (JOURNAL ONLINE OF PHYSICS, 2024)
The magmatic arc of Sumatra Island, which is indicated by the presence of the Barisan Mountains zone on the west side of Sumatra Island with a general direction northwest - southeast, makes Mount Masurai, which is administratively in Merangin Regency, Jambi Province, become one of the volcanoes on Sumatra Island. Geographically, the peak of Mount Masurai is located at coordinates 101o 51' 28.60" E and 2o 30' 09.19" S with an elevation 2915 masl. The eruption period of Mount Masurai is estimated to have occurred twice during the eruption period. Based on the lack of information about volcanoes, this research was conducted to determine the characteristic and distribution of pyroclastics from Mount Masurai. In the area around Mount Masurai, remnants of volcanic eruptions were found, in the form of pyroclastic flows and falls. From data collection based on the results of geological mapping and petrographic analysis, pyroclastic rocks were found in the area around Mount Masurai with lithology in the form of Andesite Breccia, Laharic Breccia Pumice Breccia, Lapilli stone and Tuff. This is reinforced by the results of petrographic analysis of rock samples which are dominated by the presence of a glass